A modified learning by design approach to support preservice teachers’ technology integration into teaching - Junhong, Tang; Lim, Jia Wei; Tee, Meng Yew (International Journal of Evaluation and Research in Education (IJERE), 2025)
Integrating technology into instructional practices continues to pose a substantial challenge for preservice teachers, a challenge that has not been sufficiently addressed by existing teacher education programs. This study seeks to bridge this gap by implementing, evaluating, and refining a modified learning by design (mLBD) approach through a two-cycle design-based research (DBR) methodology. The research was conducted with 27 preservice teachers in the first cycle and 29 in the second cycle. Data were collected through semi-structured interviews, group lesson plans, micro-teaching sessions, peer feedback, and group discussions. The content analysis and constant comparative analysis identified two key impediments to effective technology integration: i) a superficial understanding of teaching methods and approaches and ii) a lack of targeted instructional guidance. Conversely, three facilitating factors were found to support preservice teachers’ technology integration: i) a deep understanding of teaching methods and approaches; ii) targeted guidance from the instructor; and iii) authentic experiences in collaborative curriculum design and redesign. These findings suggest that the mLBD approach offers valuable insights for enhancing teacher education programs’ capacity to support preservice teachers in effectively integrating technology into their instructional practices.